Diferensiasi Layanan Sebagai Basis Implementasi Strategi Bisnis (Studi Kasus pada PT. Xyz) - Livia Unsri; Eddy Herjanto (Jurnal Manajemen Bisnis dan Kewirausahaan, 2020)
The purpose of this research is to identify the company’s internal and external factors, strategic planning, and service differentiation to implement the exact business strategy within the company. This research is a study case of XYZ company which moving in technology information business industry. The data in this research was collected through field and library method. The research results showed that XYZ company has implemented the service differentiation and has the above average response in facing threats and opportunities that exist in its business so that the company can use the SO strategy and expansion strategy as its business strategy.